A Presurgical‐Window Intervention Trial of Isothiocyanate‐Rich Broccoli Sprout Extract in Patients with Breast Cancer. Issue 12 (6th May 2022) - Wang, Zinian; Tu, Chengjian; Pratt, Rachel; Khoury, Thaer; Qu, Jun; Fahey, Jed W.; McCann, Susan E.; Zhang, Yuesheng; Wu, Yue; Hutson, Alan D.; Ambrosone, Christine B.; Edge, Stephen B.; et al.
Abstract : Scope: Dietary isothiocyanates (ITCs) from cruciferous vegetables have shown potent anti‐breast cancer activities in preclinical models, but their anticancer effects in vivo in breast cancer patients remain elusive. A proof‐of‐principle, presurgical window of opportunity trial is conducted to assess the anticancer effects of dietary ITCs in breast cancer patients. Methods and Results: Thirty postmenopausal breast cancer patients are randomly assigned to receive ITC‐rich broccoli sprout extract (BSE) (200 µmol ITC per day) or a placebo for 2 weeks. Expression of biomarkers related to ITCs functions are measured in breast cancer tissue specimens at pre‐ and post‐interventions using immunohistochemistry staining. First morning urine samples are collected at both timepoints for proteomic analysis. Overall, the study shows high compliance (100%) and low toxicity (no grade 4 adverse event). Trends of increase in cleaved caspase 3 and tumor‐infiltrating lymphocytes (TILs) and trends of decrease in Ki‐67 and nuclear to cytoplasm ratio of estrogen receptor (ER)‐α are observed in the BSE arm only, consistent with the significantly altered signaling pathways identified in urinary proteomic analysis. Conclusions: Anticancer activities of ITCs are observed in breast cancer patients, supporting the potential beneficial roles of ITC‐containing cruciferous vegetables in breast cancer prognosis. Abstract : Thirty postmenopausal breast cancer patients are randomly assigned to receive broccoli sprout extract (BSE) or placebo for 2 weeks before surgery. Tissue and urine samples are collected at pre‐ and post‐intervention. Trends of biomarker changes in breast cancer tissue aligned with significantly altered signaling pathways identify in urinary proteomic analysis, showing induction of apoptosis and modulation of immune function by BSE intervention.